Augustine, Pascentius, and the Theft of De Trinitate - Beckwith, Carl L. (Revue d'études augustiniennes et patristiques, 2025)
There is no scholarly consensus on when to date the public discussion between Augustine and Pascentius and their subsequent correspondence (epp. 238-241). The suggested dates range from 400 to 429. Possidius’ brief account of the discussion and Augustine’s scattered comments establish certain historical conditions necessary for any proposed date: the debate happened in Carthage, in the presence of Alypius and other distinguished people, when Pascentius served as comes domus regiae. Following the discussion, Pascentius mischaracterized the exchange and accused Augustine of failing to state his faith. Augustine wrote ep. 238 to give his account of the discussion and to state his faith in writing for Pascentius. A careful consideration of the theological and exegetical arguments of ep. 238, noting especially the correspondence of these arguments with other works by Augustine that can be more firmly dated, indicates that the letter dates sometime between 414-420. When we combine these insights from ep. 238 with the historical conditions identified by Possidius and Augustine, the likely date for the debate is the summer of 418 or 419. Although the evidence supports both dates, one additional item, the theft of De Trinitate in 418 and Augustine’s resumption of it in 419-420, lends weight to the summer of 418. If this is the case, the encounter with Pascentius, his harassment of Catholic priests and abuse of Augustine during Augustine’s time in Caesarea in Mauretania during the fall of 418, may have precipitated the unauthorized publication of De Trinitate. Although this final point cannot be proved directly, there is circumstantial evidence to support it.